A Content Analysis of Emergency Department Discharge Instructions for Acute Pediatric Febrile Illnesses: The Current State and Opportunities for Improvement. (November 2021) - Overmann, Kevin M.; Vukovic, Adam A.; Britto, Maria T.
Quality emergency department (ED) discharge communication is critical to understanding of disease progression, home management, and return instructions. Addressing social aspects of disease burden are important to improving satisfaction and healthcare utilization. The objective of this study was to understand the extent to which written ED discharge instructions address multifaceted aspects of disease to meet the comprehensive needs of families with common childhood illnesses. We analyzed a national sample of 28 written discharge instructions from pediatric EDs using thematic and inductive content analysis. Seven themes were identified. Nearly all discharge instructions devoted a majority of content to themes related to disease physiology. Other themes common to instructions were related to parental instructions for caring for the child and when to return for further care. Content on caregiver reassurance, returning to daily activities, improving well-being, and promoting community health were not a focus of discharge instructions. Inclusion of multifaceted discharge materials which address both medical and social aspects of disease may help improve family-centered emergency care and the quality of care transitions for common childhood illnesses.